Influence of nano-TiO2 particles on the microstructure, mechanical and wear behaviour of AA7178 alloy matrix fabricated by stir casting technique. (April 2023) - Bharat, Nikhil; Bose, PSC
The current study focuses on the influence of varying wt% of nano-TiO2 particles (1%, 2% and 3%) on the microstructure, mechanical and tribological properties of AA7178 alloy matrix composite produced by stir casting method. The grain boundaries of the prepared composites were revealed using an optical microscope. The uniform distribution of nano-TiO2 particles in the alloy matrix was observed by scanning electron microscope. X-ray diffraction verified the existence of reinforced nano-TiO2 particulates in the samples, and microstructural images revealed a consistent distribution of reinforcements in the matrix. The formation of more refined grains from coarser grains was observed using electron backscatter diffraction analysis. The texture analysis revealed the presence of dominant A and A2 * components with a maximum intensity of 5.137. Fractography disclosed that the reinforcements did not peel away from the alloy matrix, and the form of failure was both brittle and ductile. Abrasive wear was observed for the worn-out surface of the nanocomposites. It was observed that by increasing wt% of TiO2 nanoparticles, the mechanical and tribological properties of the alloy matrix increased compared to the base alloy. The optimum mechanical and tribological properties were obtained at 2 wt% of nano-TiO2 particulates.